2003
DOI: 10.1128/iai.71.4.2182-2191.2003
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Protection of Gnotobiotic Pigs against Experimental Salmonellosis following Induction of Polymorphonuclear Leukocytes by AvirulentSalmonella enterica

Abstract: Oral inoculation of 5-day-old gnotobiotic pigs with Salmonella enterica serovar Typhimurium strain F98 resulted in severe enteritis and invasive disease. Preinoculation 24 h earlier with an avirulent mutant of Salmonella enterica serovar Infantis (1326/28) completely prevented disease for up to 14 days (when the experiment was terminated). S. enterica serovar Infantis colonized the alimentary tract well, with high bacterial counts in the intestinal lumen but with almost no invasion into the tissues. Unprotecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 43 publications
3
53
0
Order By: Relevance
“…However, this does not rule out IL-10 production in vivo by other cell types. Recent evidence from Salmonella enterica serovar Infantis infections of gnotobitic pigs shows that polymorphonuclear leukocyte influx can be uncoupled from the disease process and preempt a virulent infection, thus protecting against challenge with virulent Salmonella (13). Obviously, therefore, factors other than the signals that attract polymorphonuclear leukocytes are required for inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not rule out IL-10 production in vivo by other cell types. Recent evidence from Salmonella enterica serovar Infantis infections of gnotobitic pigs shows that polymorphonuclear leukocyte influx can be uncoupled from the disease process and preempt a virulent infection, thus protecting against challenge with virulent Salmonella (13). Obviously, therefore, factors other than the signals that attract polymorphonuclear leukocytes are required for inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%
“…r (Serogroup C1) protected highly susceptible gnotobiotic piglets against lethal oral challenge with virulent S. Typhimurium F98 (Serogroup B) (Foster et al 2003;Foster et al 2005) when this strain was administered just 24 h after vaccination. In this case it was considered that the presence of the vaccine strain in the tissues generated a high level of nonspecific immunity which clearly acted against heterologous serogroups.…”
Section: /28фmentioning
confidence: 99%
“…In Europe, Salmonella serovar Typhimurium is the serovar that is most frequently isolated from humans or pigs (25), while in the United States it is estimated that up to 4 million cases of salmonellosis occur annually, of which about 500 are fatal (19). Although vaccination of piglets against Salmonella is a desirable target, gnotobiotic piglets have previously been shown to be a useful model of enteric disease in humans (16,20,41). Recently, we showed that oral inoculation of 5-day-old gnotobiotic piglets with a rough lipopolysaccharide (LPS) mutant of S. enterica serovar Infantis 1326/28 (1326/28⌽ r ) protects against a subsequent, normally lethal challenge with Salmonella serovar Typhimurium strain F98 (16).…”
Section: Preinoculation Of Susceptible 5-day-old Gnotobiotic Piglets mentioning
confidence: 99%
“…Although vaccination of piglets against Salmonella is a desirable target, gnotobiotic piglets have previously been shown to be a useful model of enteric disease in humans (16,20,41). Recently, we showed that oral inoculation of 5-day-old gnotobiotic piglets with a rough lipopolysaccharide (LPS) mutant of S. enterica serovar Infantis 1326/28 (1326/28⌽ r ) protects against a subsequent, normally lethal challenge with Salmonella serovar Typhimurium strain F98 (16). Furthermore, our results indicated that there is an immunological basis for this protection and that the protection is most likely due to the significant infiltration of neutrophils in the intestinal villi prior to challenge with Salmonella serovar Typhimurium strain F98.…”
Section: Preinoculation Of Susceptible 5-day-old Gnotobiotic Piglets mentioning
confidence: 99%
See 1 more Smart Citation